Understanding Homeless With Reference To Mental Health; Case Study In Georgetown, Penang - Hassan, Hafizzul Amri (2014)
The objectives of study were to: I) Identify the factors of the original/main that causes homelessness in Georgetown Penang, 2) Analyze the mental health of homeless people in Georgetown Penang, 3)Identify the needs of homeless people in Georgetown Penang, 4) To suggest possible Social Work intervention to address homeless issue in Georgetown, Penang.